MECHANISM OF ORGANIZING PHYSICAL EDUCATION AND PSYCHOLOGICAL SERVICES IN HIGHER EDUCATION INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, on the basis of the mathematical measurements of the three main components, based on the level of cognitive, psycho-emotional and stereotyping, moral, mental, aesthetic education and labor education among students of higher educational institutions are the basis for achieving high results in the process of physical education.